Perubahan Intensitas Dismenore Melalui Pemberian Massage Efflurage dan Massage Efflurage Aromaterapi Lavender pada Mahasiswi Tingkat 1 A - Hoiri, Dini Aulani Fristalia; Jamhariyah, Jamhariyah; Sasmito, Lulut (Malang Journal of Midwifery (MAJORY), 2023)
Dysmenorrhea is a common issue experienced by women before and during menstruation, including adolescent girls.Non-pharmacological treatments can be done, one of which is effleurage massage using lavender aromatherapy oil. This study aims to determine the changes in the decrease of dysmenorrhea intensity between effleurage massage and effleurage massage using lavender aromatherapy oil. This study is a non-paired comparative type of research with a two-group pretest-posttest design approach. The population consisted of 44 respondents with a sample size of 39 respondents. Group 1 received effleurage massage and Group 2 received effleurage massage using lavender aromatherapy oil. Data was collected using the NRS questionnaire, and both groups' data were tested using paired t-tests and then retested using an independent t-test to compare between the groups. The statistical tests for Group 1 produced ?1??2 and ?-value ,000 < 0.05, indicating the rejection of the null hypothesis. The same result was found for Group 2, with ?1??2 and ?-value ,000 < 0.05. The difference in the change of dysmenorrhea intensity between the two groups also yielded ?1??2 and ?-value ,000 < 0.05, leading to the rejection of the null hypothesis. There is a difference in the reduction of intensity between effleurage massage and effleurage massage using lavender aromatherapy oil. Effleurage massage using lavender aromatherapy oil showed a significant decrease in dysmenorrhea intensity. This is because effleurage massage not only distracts pain but lavender aromatherapy also produces endorphins, thus modifying pain perception in the brain. Therefore, it can be an alternative choice in reducing dysmenorrhea intensity.